Tratamiento contable de propiedad planta y equipo en el Municipio de Santa Rosa Provincia de El Oro - Cabrera Ojeda, Angie Mirella (2020)
The present case study on the accounting treatment of property, plant and equipment was taken as an information center to the centralized Autonomous Government of the Santa Rosa canton of the El Oro province, addressed to the vehicle item where a series of shortcomings in the inventories (vehicle) there is a bad application in the registration, valuation and classification of goods that does not comply with the provisions of government accounting regulations, the institution has twenty-one vehicles which is made up of dump trucks, trucks and motorcycles. There are damaged and lost vehicles, motorcycles which are still registered in inventories as existing assets of the company, other deficiencies found are the existence of dump trucks registered in vehicles which belong to machinery and equipment and estimate a useful life different from that of the vehicle, in addition to the existence of motorcycle cars that have reached their useful life, and which keep the warehouse - The winery has not given the respective derecognition of said asset, therefore the accountant does not have updated information on fixed assets, which we were able to conclude that they do not comply with the laws that govern the institutions, due to the lack of training on the system that uses the institution for their respective depreciations, which is essential to know the accumulated depreciation of each year of fixed assets and also the book value, so the institution can control the process of use of property, plant and equipment to optimize the Institution resource.